Influence of Type Cooperative Learning Model Two Stay Two Stray On Student Mathematics Learning Outcomes - Nurija, Siti Nurija; Sridana, Nyoman; Kurniawan, Eka (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2023)
This research aims to determine the effect of the cooperative learning model typeTwo Stay Two Stray (MP-TSTS) on the mathematics learning outcomes of class VIII students at MTs Al Aziziyah Putra Gunungsari. The type of research used is quantitative descriptive researchPost-test Only Control Design. The population in this study were all class VIII students at MTs Al Aziziyah Putra Gunungsari, consisting of 8 classes. The sample in this research was students in classes VIII A and VIII B. The instrument used in this research was a learning outcomes test. The data collected consists of student learning outcomes data. Data were analyzed using descriptive analysis. Results of inferential analysis using test independent sample t-test with the help ofSPSS 23 to test the hypothesis shows that the student learning outcomes data on post-test, gain normalized and student learning outcomes data with a significant value (2-tailed) < 0.05, namely 0.029. So the learning outcomes of students who use MP-TSTS and students who use the small group discussion method are significantly different. This means that MP-TSTS has an effect on improving learning outcomes. Based on the results of the inferential analysis, it can be concluded that the implementation of MP-TSTS is effective/influenced on the mathematics learning outcomes of class VIII students at MTs Al Aziziyah Putra Gunungsari for the 2022/2023 academic year.